Yohimbine-induced withdrawal and anxiety symptoms in opioid-dependent patients - Stine, Susan M; Southwick, Steven M; Petrakis, Ismene L; Kosten, Thomas R; Charney, Dennis S; Krystal, John H (Biological psychiatry (1969), 2002)
Background: Alteration in noradrenergic regulation as well as alteration in the hypothalamic—pituitary—adrenal (HPA) axis have been associated with opioid dependence and acute abstinence symptoms. Methods: This double-blind, placebo-controlled study evaluated subjective, physiologic, and biochemical responses to yohimbine (.4 mg/kg, IV) in eight patients receiving methadone and compared results to those from a pool of nine healthy volunteers. All subjects were compared for panic anxiety symptom scale (PASS) scores, systolic and diastolic blood pressure, heart rate, plasma 3-methoxy-4 hydroxyphenethyleneglycol (MHPG), and cortisol. Results: Yohimbine elicited objective and subjective opioid withdrawal and elevated craving for opioid drugs in methadone patients. Significant yohimbine effects were seen across the combined subject group for PASS, physiologic measures, MHPG, and cortisol. Methadone patients had lower baseline MHPG levels. Methadone group interactions with yohimbine were seen for systolic blood pressure and cortisol levels. Conclusions: Methadone-maintained patients are sensitive to the postsynaptic effects of noradrenergic-facilitating medications, experiencing greater physiologic and psychological symptoms, including an increase in craving. The effect on cortisol supports the above conclusion and is consistent with HPA axis perturbation in opioid dependence as reported in other studies and extends these observations to stable methadone-maintained patients. Medications that increase synaptic noradrenaline should be used with care in opioid-dependent patients.